Development of an inhalation unit risk factor for ethylene dibromide. (7th June 2017) - Schaefer, Heather R.; Myers, Jessica L.
Abstract: The Texas Commission on Environmental Quality (TCEQ) follows standard scientific methods to develop up-to-date toxicity factors for chemicals emitted in the state of Texas. An inhalation unit risk factor (URF) was developed for ethylene dibromide (EDB, CAS 106-93-4) based on an increased incidence of nasal cavity adenocarcinomas observed in female rats in a 2-year inhalation cancer bioassay conducted by the National Toxicology Program (NTP). The NTP study provided evidence of several EDB-induced tumors in male and female rats and in female mice. Tumor incidences that were statistically increased at the low dose and that showed a statistically significant increasing trend were considered in identifying the critical effect. Following benchmark concentration (BMC) modeling and animal-to-human dosimetric adjustments, the increased incidence of nasal cavity adenocarcinomas observed in female rats was determined to be the most sensitive tumorigenic effect in the most sensitive species and sex and was utilized as the carcinogenic endpoint for the development of the URF. The 95% lower confidence limit of the BMC at the 10% excess risk level (BMCL10 of 292.8 ppb) was determined for calculation of the URF. The resulting URF based on increased nasal cavity adenocarcinomas observed in female rats is 3.4E-04 per ppb (4.4E-05 per µg/m 3 ). The lifetime air concentration corresponding to a no significant excess risk level of one in 100, 000 is 0.029 ppb (0.22 µg/m 3 ), which is considered sufficiently health-protective for use in protecting the general public against the potential carcinogenic effects of chronic exposure to EDB in ambient air.